2018
DOI: 10.1111/cei.13226
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of activated neutrophils correlates with disease severity in adult Crohn’s disease

Abstract: Summary Neutrophils are detected in inflamed colon in Crohn’s disease (CD). However, whether the frequency and/or activation of circulating or gut tissue neutrophils correlate with endoscopic severity remains to be investigated. A cohort of 73 CD patients was prospectively enrolled according to endoscopic severity and treatment history. Individuals with active disease were stratified using the Montreal classification. Harvey–Bradshaw Index (HBI) and Simple Endoscopic Score for Crohn’s Disease (SES‐CD) were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 63 publications
1
28
0
1
Order By: Relevance
“…These results suggested that neutrophils are essential for CD progression; however, whether its role is pathological or beneficial remains controversial. Recently, singlecell analysis revealed that neutrophils recruitment and activation was correlated with clinical disease severity in CD (Therrien et al, 2019). However, Zhou et al (2018) demonstrated that the CD177 + neutrophils showed a protective effect in IBD through increased anti-bacterial activity and IL-22 production.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that neutrophils are essential for CD progression; however, whether its role is pathological or beneficial remains controversial. Recently, singlecell analysis revealed that neutrophils recruitment and activation was correlated with clinical disease severity in CD (Therrien et al, 2019). However, Zhou et al (2018) demonstrated that the CD177 + neutrophils showed a protective effect in IBD through increased anti-bacterial activity and IL-22 production.…”
Section: Discussionmentioning
confidence: 99%
“…16 They also released a host of proteases, proinflammatory cytokines and mediators such as IL-8, TNF-a, and leukotriene B 4 that damage the epithelial barrier and recruit monocytes and more neutrophils to the gut. 17,18 Neutrophil infiltration correlates with disease activity in IBD [19][20][21][22][23] and is a widely used and reliable component of UC disease scoring systems. 24 Calprotectin (s100A8/9), the most widely used biomarker in IBD, constitutes up to 60% of neutrophil cytosolic proteins.…”
Section: The Role Of Neutrophils In Ibdmentioning
confidence: 99%
“…Notably, the dysregulated transformation of infiltrating monocytes to pro-inflammatory cytokine producing cells, as well as altered macrophages with ability to induce T H 17 differentiation in patients with IBD, suggest the relevance of innate immune cells as triggers of pathogenic intestinal inflammation [79,81]. On the other hand, the significant recruitment of neutrophils is well-described in IBD patients, but their role is contradictory, as some reports suggest their advantageous role during intestinal inflammation, while others described tissue damaging effects [82,83].…”
Section: Definition Of Immune Cell Signaturementioning
confidence: 99%